Surviving & Thriving; a healthy lifestyle app for new US firefighters: usability and pilot study protocol - Hershey, Maria Soledad; Bouziani, Eleni; Chen, Xin Yu (Maggie); Lidoriki, Irene; Hadkhale, Kishor; Huang, Ya-Chin; Filippou, Theodoros; López-Gil, José Francisco; Gribble, Anne Katherine; Lan, Fan-Yun; Sotos-Prieto, Mercedes; Kales, Stefanos N. (Frontiers in Endocrinology, 2023)
In the United States (US), new firefighters' fitness and health behaviors deteriorate rapidly after fire academy graduation. Over the long-term, this increases their risks for chronic diseases. This study protocol describes the proposed usability testing and pilot study of a newly designed and developed healthy lifestyle smartphone app, "Surviving & Thriving", tailored towards young US firefighters. "Surviving & Thriving" will provide interactive educational content on four lifestyle factors; nutrition, sleep, physical activity, and resilience, and include a personalized journey, habit tracker, and elements of gamification to promote engagement and long-term healthy behavior change. The first phase of the app development entails alpha testing by the research team and pre-beta testing by a fire service expert panel which will help refine the app into a pre-consumer version. Upon completion of the full app prototype, beta 'usability' testing will be conducted among new fire academy graduates from two New England fire academies to collect qualitative and quantitative feedback via focus groups and satisfaction surveys, respectively. A last phase of piloting the app will evaluate the app's efficacy at maintaining/improving healthy lifestyle behaviors, mental health metrics, and physical fitness metrics. We will also evaluate whether firefighters' perceived "health cultures" scores (ratings of each fire station's/fire department's environments as to encouraging/discouraging healthy behaviors) modify the changes in health metrics after utilizing the app for three to six months. This novel user-friendly app seeks to help new firefighters maintain/improve their health and fitness more effectively, reducing their risk of lifestyle-related chronic disease. Firefighters who can establish healthy habits early in their careers are more likely to sustain them throughout their lives.